Glucocorticoid receptor Bcl I variant is associated with an increased atherogenic profile in response to long-term overfeeding - Ukkola, Olavi; Rosmond, Roland; Tremblay, Angelo; Bouchard, Claude (Atherosclerosis, 2001)
The effect of the glucocorticoid receptor (GRL) gene Bcl I polymorphism on body composition and metabolic changes in response to overfeeding was studied. Twenty-four men (mean age 21±2 years) who constituted 12 pairs of identical twins ate a 4.2 MJ/day energy surplus, 6 days a week, during a period of 100 days. The GRL Bcl I marker was identified by Southern Blot technique. Total body fat was assessed by hydrodensitometry and abdominal fat areas were measured by computed tomography. Fasting plasma glucose and insulin during an oral glucose tolerance test (OGTT) were assayed. The insulin and glucose areas were computed using the trapezoidal method. Triglyceride and cholesterol concentrations in plasma and lipoprotein fractions were determined enzymatically. The results showed that overfeeding induced a greater increase in body weight ( p=0.002) in the 2.3/2.3 kb ( n=12) than in the 4.5/2.3 kb ( n=12) subjects. In addition, plasma levels of total ( p=0.007) and low-density lipoprotein (LDL) cholesterol ( p=0.003), as well as systolic blood pressure ( p=0.036) increased more in the 2.3/2.3 kb than in the 4.5/2.3 kb subjects. The 2.3/2.3 kb genotype was also associated with a greater increase in abdominal visceral fat ( p=0.040) compared to the 4.5/2.3 kb genotype. In conclusion, 2.3/2.3 kb subjects of the GRL Bcl I polymorphism experience greater increases in body weight, blood pressure and cholesterol levels as well as visceral fat than 4.5/2.3 kb subjects in response to overfeeding. These data suggest that overfeeding induces an atherogenic profile in subjects who are homozygotes for the 2.3 kb allele.